Best Practice Protocols for Physique Assessment in Sport - Ducker, Kagan; Kerr, Deborah; Hume, P. (2018)
Physique assessment provides valuable information to the athlete and coach. However, taken in isolation physique assessment can easily be misinterpreted or misused. Additional information, such as the dietary intake and training load, and input from exercise and health professionals is required to fully interpret the findings and make recommendations. Strengths and limitations of methods of physique assessment are outlined, along with best practice approaches to collection and reporting of data.